An assessment of the status of the metalworking industries in Western Visayas - Pachoco, Faye C.; Capuyan, Fritz F.; Castro, Ryan R.; Doligosa, Louie L.
Metals has now become almost a basic commodity especially in this age of technological advancements. Much emphasis have been given to the protection and preservation of the environment in these times. Thus, giving the existence of metals a lot more significance than ever. But then, metals can never be put into its proper use without the application of certain processes that would convert it to a useful piece of material. Thus, the introduction of metalworking. Metalworking has been very useful not only to the industrial sectors but in almost any sector there is in the society. In Western Visayas for instance, metalworking made life easier for farmers and has helped brought fame to the province but producing agricultural implements which hastened the jobs which were once done manually. However, the industry seems to have taken the backseat recently. Not much is heard from their side. It seems like their industry is dying. This is then where this research takes off. This study aims to evaluate the present conditions of the metalworking industry in Western Visayas by identifying the problems it is faced with and recommending solutions if there are possible ones. A total of 40 respondents were then gathered to answer the question specifically framed to cater the objectives of this study. A simple statistical tool in the form of the frequency analysis was used to evaluate the results of the survey conducted in relation to this study.